2003
DOI: 10.1017/s0952523803205046
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-vision in a patient with central and paracentral vision loss reflects cortical reorganization

Abstract: SM, a 21-year-old female, presents an extensive central scotoma (30 deg) with dense absolute scotoma (visual acuity = 10/100) in the macular area (10 deg) due to Stargardt's disease. We provide behavioral evidence of cortical plastic reorganization since the patient could perform several visual tasks with her poor-vision eyes better than controls, although high spatial frequency sensitivity and visual acuity are severely impaired. Between 2.5-deg and 12-deg eccentricities, SM presented (1) normal acuity for cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…In explaining the lack of the crowding effect for MD patients it should be noted that for MD2 and MD3 critical spacing was already very low before PL, confirming the evidence of a major use-dependent responsiveness of eccentric vision in MD patients (Casco et al, 2003;De Stefani, Pinello, Campana, Mazzarolo, Lo Giudice, & Casco, 2011) and an overall reduced crowding effect for the PRL location in MD patients without previous training (Chung, 2011).…”
Section: Fig 7 About Here]mentioning
confidence: 49%
See 2 more Smart Citations
“…In explaining the lack of the crowding effect for MD patients it should be noted that for MD2 and MD3 critical spacing was already very low before PL, confirming the evidence of a major use-dependent responsiveness of eccentric vision in MD patients (Casco et al, 2003;De Stefani, Pinello, Campana, Mazzarolo, Lo Giudice, & Casco, 2011) and an overall reduced crowding effect for the PRL location in MD patients without previous training (Chung, 2011).…”
Section: Fig 7 About Here]mentioning
confidence: 49%
“…This aspect should be taken into account when planning a training protocol for MD patients who often have non-localized PRL or more than one PRL (Timberlake et al, 1987). However, since it is unpractical to use eye movements recording during PL, it should be considered whether it is more appropriate to present randomly the stimuli either in the right or in the left visual hemi-field for very short durations, a procedure that reduces eye movements (Casco et al, 2003) or simply train the PRL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Casco et al (2003) recently reported on a comparison in parafoveal and peripheral visual function between a 21-year-old JMD patient and a group of normally sighted control participants. Casco et al found comparable or even better performance from the JMD patient in some of the parafoveal and peripheral visual tasks including lexical decision, recognition of crowded letters and visual search.…”
Section: Retinotopy-driven Explanation Of Prlmentioning
confidence: 99%
“…The success of some patients with macular degeneration in the successful negotiation of activities of daily life indicates that the brain is capable of compensation for this disruption. [8][9][10] If we can understand this natural process, we may be able to enhance this process for other patients during visual rehabilitation.…”
mentioning
confidence: 99%